The form and functions of newcomer EAL students' speech in English: patterns of progression and communication in semi-structured interview dialogue. (2nd January 2019) - Evans, Michael; Fisher, Linda; Forbes, Karen; Liu, Yongcan
ABSTRACT: Analysis of progression in spoken English by newcomer migrant-background learners has traditionally oscillated between formal assessment of oral proficiency and ethnographic description of naturally occurring peer discourse. This paper reports on data gathered from a longitudinal study of newly arrived students with English as an additional language (EAL) in secondary schools in England. The corpus examined consists of semi-structured interviews with 22 students of different L1 backgrounds, each interviewed twice within a 12-month interval. Findings reveal marked improvement in comprehension with greatly reduced reliance on interpreters and clarification requests; limited range in use of verb tense, with heavy reliance on the present tense; areas of improvement in communicative function of speech mainly limited to conjecture, likes and dislikes, and expressions of feeling. Progression in the use of reported speech was limited for the group as a whole but where it was used it shed light on the individual's language development and into their views on their social experiences in their new environment. We argue that there is an urgent need for EAL practitioners and researchers to measure language development along similar lines in order to ground future policy-making in evidential knowledge of patterns of development in oral expression in English.